TRANSFORMATION OF TWO MUTUALLY CONNECTED MODELS FOR CONVECTIVE HEATING OF WOOD DETAILS BEFORE THEIR LACQUERING IN A FORM, SUITABLE FOR PROGRAMMING - Deliiski, Nencho; Trichkov, Neno; Gochev, Zhivko; Angelski, Dimitar (Innovation in Woodworking Industry and Engineering design, 2017)
Using the explicit form of the finite-difference method, two suggested by the authors mutually connected mathematical models have been transformed in a form, suitable for programming. For the numerical solution of the transformed models, a software program has been prepared in the calculation environment of Visual Fortran Professional. With the help of the program, the 1D distribution of the temperature along the thicknesses of flat oak details and of their carrying transport rubber band with hw = 16 mm, lw = 0.6 m, u = 0.08 kg.kg-1, hB = 4 mm, bB = 0.8 m, and t0 = 20 oC, during unilateral convective heating for a period of 10 min at tha = 100 oC, vha = 2 m·s-1, 5 m·s-1, 8 m·s-1, and tnha = 20 ºC in order to ensure suitable thermal conditions for the subsequent details’ lacquering has been calculated, visualized and analyzed.